2015
DOI: 10.1021/ja511204p
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Ligand Binding to UDP-Galactopyranose Mutase from Mycobacterium tuberculosis Using Substrate and Tetrafluorinated Substrate Analogues

Abstract: UDP-Galactopyranose mutase (UGM) is a flavin-containing enzyme that catalyses the reversible conversion of UDP-Galactopyranose (UDP-Galp) to UDP-Galactofuranose (UDPGalf) and plays a key role in the biosynthesis of the mycobacterial cell wall galactofuran. A soluble, active form of UGM from Mycobacterium tuberculosis (MtUGM) was obtained from a dual His 6 -MBP tagged MtUGM construct. We present the first complex structures of MtUGM with bound substrate UDP-Galp (both oxidized flavin and reduced flavin). In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 97 publications
4
64
0
Order By: Relevance
“…In this way, Y364 may prevent the inhibitor from binding CdUGM in the closed conformation. A similar inward-oriented position of the Y364 equivalent was observed in the closed structure of MtUGM 26 . Notably, no such conformational change of the corresponding residue (Y349) was detected in KpUGM (Figure 7C) 28 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this way, Y364 may prevent the inhibitor from binding CdUGM in the closed conformation. A similar inward-oriented position of the Y364 equivalent was observed in the closed structure of MtUGM 26 . Notably, no such conformational change of the corresponding residue (Y349) was detected in KpUGM (Figure 7C) 28 .…”
Section: Discussionsupporting
confidence: 75%
“…Many known inhibitors are UDP-Gal f analogs that bind UGM in vitro but have not been shown to function in cells. 19-26 Our group identified non-substrate analogue 2-aminothiazoles as some of the most potent UGM inhibitors described to date 14 (Figure 1). These compounds, however, exhibited some toxicity to mammalian cells and were difficult to optimize.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that during the formation of UDP-Galf, a flavin adenine dinucleotide (FAD)-iminium ion intermediate is formed through nucleophilic addition that facilitates galactose ring opening and contraction (5,(12)(13)(14)(15)(16). Three dimensional structures for members of the UGM family have been determined by X-ray crystallography in free form and in complex with various substrates, as well as in association with both oxidized and reduced forms of FAD (12,13,(17)(18)(19). Notably, a covalent FAD-Galp intermediate involved in the UGM reaction has recently yielded to elucidation by X-ray crystallography shedding significant insight into UGM catalysis (20).…”
mentioning
confidence: 99%
“…Sanders et al [6][7][8] showed from the crystal structure of UGM in E.coli that the diphosphate group of UDP-Galp forms ionic interactions with key amino acids R247 and R278 and that Y181, Y311 and Y346 are important for substrate binding through hydrogen bonding with the carbohydrate ring; W156 stacks against the ribose moiety. Schaefer et al 9,10 proposed that the ionic pyrophosphate group could be replaced by a nonionic group to increase bioavailability and facilitate penetration of cells and cell compartments to reach the target enzymes.…”
mentioning
confidence: 99%
“…The low activity may be due to the absence of the ionic charge in the diphosphate bridge that induces loop closure8,16,19 as well as the length of the polyhydroxylated chain, the Galp.and uracil moieties been unable to form optimal contacts in their respective subsites. Further optimization efforts through more refined molecular dynamicscalculations with the very recently published crystal structure of UGM from M. tuberculosis 8 should shed light on this issue and lead to the design of additional non-ionic substrate mimics.…”
mentioning
confidence: 99%